2022
DOI: 10.3390/math10122075
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Time Reproduction Number in Kupang City Indonesia, 2016–2020, and Assessing the Effects of Vaccination and Different Wolbachia Strains on Dengue Transmission Dynamics

Abstract: The use of a vaccine and Wolbachia bacterium have been proposed as new strategies against dengue. However, the performance of Wolbachia in reducing dengue incidence may depend on the Wolbachia strains. Therefore, in this paper, the performance of two Wolbachia strains which are WMel and WAu, in combination with the vaccine, has been assessed by using an age-dependent mathematical model. An effective reproduction number has been calculated using the Extended Kalman Filter (EKF) algorithm. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…In future work, it would be valuable to explore the potential of other differential equation-based compartmental models that take into account vector-host-mitigation strategies (vaccination or Wolbachia bacterium inoculation) as interactions [44] , [45] , [43] . Such models have been used in the past to evaluate the impact of local vector eradication and control efforts carried out by Health authorities [76] , [77] , [78] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work, it would be valuable to explore the potential of other differential equation-based compartmental models that take into account vector-host-mitigation strategies (vaccination or Wolbachia bacterium inoculation) as interactions [44] , [45] , [43] . Such models have been used in the past to evaluate the impact of local vector eradication and control efforts carried out by Health authorities [76] , [77] , [78] .…”
Section: Discussionmentioning
confidence: 99%
“…Investigative efforts in vector-borne pandemics have leveraged ordinary differential equations (ODEs) as a valuable tool to guide the development of effective control strategies. The SIR and SIR-SI models, for instance, have been widely employed to determine optimal vaccination schedules and assess the efficacy of various control methods, as demonstrated in several recent studies [43] , [44] , [45] .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Salah satu alat analisis yang efektif dalam memahami dinamika penyebaran penyakit pada suatu populasi adalah model matematika [3], [4]. Elemen yang penting dalam mengkaji model matematika adalah bilangan reproduksi dasar ( ℛ 0 ) dimana bilangan reproduksi dasar tersebut merupakan ambang batas dalam menentukan keendemikan suatu penyakit [5]. Pada tulisan ini nilai bilangan reproduksi Jurnal Diferensial, Volume 04, Nomor 02, November 2022 E-ISSN: 2775-9644 dasar diestimasi berdasarkan data real yang tersedia dilapangan, dan teknik perhitungan estimasi nilai ℛ 0 merujuk pada tulisan [6]- [8].…”
Section: Pendahuluanunclassified
“…w Mel and w MelPop strains). Some recent studies compared two different and separate Wolbachia strains: w Au and w Mel 40 , w AlbB and w Mel 1 , and w AlbB/ w MelCS and w Mel 6 . The authors in 40 investigated the use of vaccination and two Wolbachia strains ( w Au and w Mel) to reduce dengue incidence and showed that although both strains can be used to mitigate dengue, w Au performed better than w Mel.…”
Section: Introductionmentioning
confidence: 99%